1996
DOI: 10.1111/j.1469-8137.1996.tb04348.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of arbuscular mycorrhizal fungi in natural ecosystems – a key to understanding the ecology and functioning of the mycorrhizal symbiosis

Abstract: SUMMARYThe mi'corrhizal symbiosis formed between plant roots and the arbuscular mycorrhizal (AM) fungi or Glomales is of great interest to ecologists because of its potential influence on ecosystem processes, its role in determining plant diversity m natural communities and the ability of the fungi to induce a wide variety of growth responses in coexisting plant species. Little attention, however, has been paid to the ecological role of diversity of AM fungi. Difficulties in identification, the inability to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 64 publications
(55 reference statements)
1
55
0
10
Order By: Relevance
“…The traditional solution for bacterial and fungal symbionts has been culturing. However, in some symbioses, what is successfully cultured does not necessarily reflect the actual community present in intact associations; and in other systems, symbionts cannot presently be cultured 11, [26][27][28] . For these reasons, molecular analyses have played a critical role both in genetically characterizing isolated mutualists and in screening assemblages directly to assess the nature of symbiont communities.…”
Section: Identifying the Playersmentioning
confidence: 99%
See 3 more Smart Citations
“…The traditional solution for bacterial and fungal symbionts has been culturing. However, in some symbioses, what is successfully cultured does not necessarily reflect the actual community present in intact associations; and in other systems, symbionts cannot presently be cultured 11, [26][27][28] . For these reasons, molecular analyses have played a critical role both in genetically characterizing isolated mutualists and in screening assemblages directly to assess the nature of symbiont communities.…”
Section: Identifying the Playersmentioning
confidence: 99%
“…For these reasons, molecular analyses have played a critical role both in genetically characterizing isolated mutualists and in screening assemblages directly to assess the nature of symbiont communities. The resulting discoveries of stunning and unexpected diversity have transformed our understanding of mutualisms involving corals (Box 1), leaf-cutter ants (Box 4), and root symbionts 26,27,29 , among others.…”
Section: Identifying the Playersmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the lack of sexual reproduction in AMF, it has been suggested that applying the species concept could be difficult and that it would be more appropriate to base the description of biodiversity on genetic diversity (Sanders et al 1996). However, even for interpretation of the most recent molecular ecological studies, genetic variation within one population and among different isolates of one species can be quite high (Antoniolli et al 2000;Clapp et al 2001;Redecker et al 2003).…”
Section: Species Richness and Community Diversity Across Chinamentioning
confidence: 99%